Social Progress and Economic Growth based on Simultaneous Equations of Panel Data - Seyed Ehsan Hosseinidoust; Akbar Khodabakhshi; Saeedeh Ahmadi (پژوهشهای اقتصادی, 2024)
Aim and Introduction Achieving a high GDP requires an answer to the question of the factors that determine GDP. Social progress is one of the important and influential factors on the GDP. The Social Development Index is a scale for measuring social well-being, which is a completely new way of looking at well-being among countries in the world without referring to GDP. On the other hand, considering the fact that economic and social indicators must be improved as preconditions for increased  living standards, which would be only possible in the shadow of economic growth, assumes it as a critical component contributing into improvement of social indicators. In this study, the mutual relationship between social progress index and GDP per capita for selected member countries of the Organization of Islamic Cooperation, during the period of 2012-2021 is investigated. The countries studied in this research are: Albania, Algeria, Azerbaijan, Bahrain, Bangladesh, Benin, Cameroon, Egypt, Guinea, Indonesia, Iran, Jordan, Kazakhstan, Kyrgyzstan, Lebanon, Malaysia, Mali, Mozambique, Niger, Nigeria, Oman, Pakistan, Saudi Arabia, Senegal, Tunisia, Turkey and UAE. Since the member countries of the Organization of Islamic Cooperation are developing countries, due to problems such as lack of human skills, inefficiency in production, lack of technological development, as well as the lack of expertise needed to produce and export competitive goods, have not been able to make significant progress in economic growth and development. Therefore, it seems that in these countries, development can be realized with social progress by paying attention to the issue of education and the basic needs of human resources in order to form and develop human capital. Investing more in human power has increased the level of productivity of production factors and technological development, and in this way, it is able to provide the necessary ground for the development of international trade and to achieve higher economic growth. Methodology In this research, the statistics related to social progress and GDP per capita in 27 member countries of the Organization of Islamic Cooperation, which are respectively taken from the social progress index and the World Bank in the years 2012 to 2021, have been used. In order to investigate the relationship between social progress and GDP, the simultaneous equation system approach in the form of the three-stage least square method (3SLS) has been applied` using Stata software. In the application of the system of simultaneous equations, it is necessary to have two recognizability conditions, which include the degree and rank condition. For this purpose, before estimating the model, these conditions have been examined first, and then preliminary tests of the model specification, such as the cross-sectional correlation test in the disturbance component, the unit root test of the combined data, the cointegration and endogeneity test have been performed. Findings The results of the data estimation over the period showed that in the model of GDP, social progress index, economic freedom and government consumption expenditure have an increasing and significant effect on the GDP per capita of the studied countries. The trade openness variable also has a negative and non-significant effect on GDP per capita. In the model related to the social progress index, the global innovation index, education index and GDP per capita have a positive and significant effect on the social progress index. The urban population variable also has a negative and insignificant effect on the social progress index. Discussion and Conclusion The results of the model estimation show that the social progress index variable in the per capita GDP model has the greatest impact on the per capita GDP among other influencing variables. The contribution of social progress into the performance of the economy and development process can be considered through reducing inequality and poverty, increasing market efficiency, economic growth, reducing costs, increasing the efficiency of human resources and capital, creating economic institutions and organizations and improving their performance, and increasing investment and employment, as well as increasing innovation and technology. The results of the estimation of the social progress index model also show the presence of a positive and significant effect of GDP per capita on the social progress index. In other words, with the increase of GDP per capita, many basic human needs such as nutrition and health care, water, health, shelter and personal safety, which is one of the indicators of social progress, are improved. In addition, in the mentioned model, the education index among other influential variables has more weight in influencing the social progress index. In other words, manpower training improves welfare infrastructure as well as opportunities, which are two dimensions of the social progress index. Finally, according to the results obtained from both models, which confirm the existence of a positive and significant relationship between the social progress index and GDP per capita, it can be concluded that there is a complementary relationship between these two variables